Can Acute Postoperative Pain Management After Tumour Resection Surgery Modulate Risk of Later Recurrence or Metastasis? - Moorthy, Aneurin; Eochagáin, Aisling Ní; Buggy, Donal J. (Frontiers in Oncology, 2021)
Background Cancer is a leading cause of mortality worldwide, but death is rarely from the primary tumour: Rather it is multi-organ dysfunction from metastatic disease that is responsible for up to 90% of cancer-related deaths. Surgical resection of the primary tumour is indicated in 70% of cases. The perioperative stress response, tissue hypoxia at the site of surgery, and acute pain contribute to immunosuppression and neo-angiogenesis, potentially promoting tumour survival, proliferation, and metastasis. Poorly controlled acute postoperative pain decreases Natural Killer (NK) immune cell activity, which could potentially facilitate circulating tumour cells from evading immune detection. This consequently promotes tumour growth and distal metastasis. Methods We conducted a comprehensive literature search for links between acute pain and cancer outcomes using multiple online databases. Relevant articles from January 1st, 2010 to September 1st, 2021 were analysed and appraised on whether postoperative pain control can modulate the risk of recurrence, metastasis, and overall cancer survival. Results Although experimental and retrospective clinical data suggest a plausible role for regional anaesthesia in cancer outcome modulation, this has not been supported by the single, largest prospective trial to date concerning breast cancer. While there are mixed results on anaesthesiology drug-related interventions, the most plausible data relates to total intravenous anaesthesia with propofol, and to systemic administration of lidocaine. Conclusion The hypothesis that anaesthetic and analgesic technique during cancer surgery could influence risk of subsequent recurrence or metastasis has been prevalent for >15 years. The first, large-scale definitive trial among women with breast cancer found robust equivalent findings between volatile anaesthesia with opioid analgesia and regional anaesthesia. Therefore, while regional anaesthesia during tumour resection does not seem to have any effect on cancer outcomes, it remains plausible that other anaesthetic techniques (e.g. total intravenous anaesthesia and systemic lidocaine infusion) might influence oncologic outcome in other major tumour resection surgery (e.g. colorectal and lung). Therefore, another large trial is needed to definitively answer these specific research questions. Until such evidence is available, perioperative analgesia for cancer surgery of curative intent should be based on patient co-morbidity and non-cancer endpoints, such as optimising analgesia and minimising postoperative complications.